Dampak Tax Planning, Digitalisasi Layanan Pajak, dan Religiusitas Terhadap Kepatuhan Wajib Pajak - Mufarrokhah, Saidatul; Mawardi, M. Cholid; Nandiroh, Umi (Universitas Islam Malang, 2024)
This research aims to assess the influence of tax planning, digitalization of tax services, and religiosity on taxpayer compliance in Micro, Small and Medium Enterprises (MSMEs) registered at DISPORAPAR Sidoarjo. Tax planning, digitalization of tax services, and religiosity are considered as independent variables, while taxpayer compliance is the dependent variable. The research methodology used in this research is quantitative by utilizing numerical data. Primary data was collected through questionnaires. The target population is MSMEs registered at DISPORAPAR Sidoarjo, with the sample size determined using the Slovin formula to obtain 75 respondents. Hypotheses were tested through various statistical analyzes including descriptive statistics, instrument testing, normality tests, classical assumption tests, moderated regression analysis, and hypothesis testing using SPSS Version 29. The findings showed that tax planning had no significant effect on taxpayer compliance, while digitalization of planning Tax does not have a significant effect on taxpayer compliance. Tax services have a positive and significant effect on taxpayer compliance. Apart from that, religiosity also has no effect on taxpayer compliance.Keywords: Tax planning, digitalization of tax services, religiosity, taxpayer compliance.